Analisis Peran Bahasa sebagai Alat Komunikasi dalam Membangun Kesetaraan Gender: Kajian Sosiolinguistik dalam Film Mulan - Rida Zahwa Melati (ELATICS JOURNAL, 2024)
This research is entitled “Analysis the role of language as a communication tool in building gender equality in the Mulam Movie:Sociolinguistics Study”. The objectives of this study is to identify whether there are differences in language use between male and female characters in the “Mulan” movie that illustrate gender equality. The formulation of the problem is whether there are differences in language use between male and female characters in the “Mulan” movie that illustrate gender power dynamics. This research uses descriptive - qualitative method to analyze and collect data. The theory used in this research is the theory proposed by William Labov (1927). The results of the research found that in the Mulan movie there are differences in the use of language between male and female characters that illustrate the dynamics of gender power, such as in the dialog between Mulan's parents that reflect gender stereotypes and different views on gender roles. Keywords: gender equality, sociolinguistics study, Mulan movie.